Pengaruh Pertumbuhan Cacing Sutra Terhadap Perbedaan Pakan Limbah Organik Dan Pakan Fermentasi - Nisayangin Mariana Daeli; Julilis Suganda Mendrofa; Karya Haga Mendrofa; Desniwati Zai; Sertifikat Waruwu; Betzy Victor Telaumbanua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Cultivation of silk worms (Tubifex sp.) is one of the important components in supporting the aquaculture sector, especially as a natural food for larval and fry fish. This study aims to assess the differences in the growth of silk worms fed with feed made from organic waste in the form of papaya residue and fermented feed made from tofu pulp, bran, sugar, brown sugar, and EM4. The study used an experimental method with a complete randomized design (CRD) consisting of two treatments, each with three replicates. Parameters observed included silk worm biomass growth, feed conversion efficiency, survival rate, and feed residue left in the media. The results showed that feeding papaya waste provided faster growth and body division of silk worms compared to fermented feed. In addition, the media fed with papaya feed showed lower levels of feed residue, resulting in a more stable culture medium with low ammonia levels. In contrast, the fermented feed left white granules that were difficult to decompose and became a source of ammonia accumulation. Thus, papaya waste feed is more recommended in the environmentally friendly and efficient cultivation of silk worms.